Beverly Hills cop II [videorecording (DVD)] - Scott, Tony, 1944-2012; Murphy, Eddie, 1961-; Reinhold, Judge, 1957-; Prochnow, Jürgen; Cox, Ronny; Ashton, John, 1948-; Reiser, Paul (Paramount, 2001)
This sequel presents further adventures of Axel Foley, a brash, street smart Detroit detective, as he comes up against a gang of munitions smugglers in Southern California.